The amygdalo-hypothalamic interaction in brain-stimulation reward. - Kane, Frank M. (University of Ottawa (Canada), 1991)
In the first experiment, the extent and distribution of self-stimulation foci within the amygdala were mapped using moveable electrodes. Amygdaloid rate-frequency functions were obtained for all positive sites tested. The pulse period required to maintain criterial responding was then calculated using a curve fitting procedure. Self-stimulation was found throughout the amygdaloid complex, with the exception of the lateral amygdaloid nucleus. Depending on brain site, maximum self-stimulation rates varied from 3 to 37 presses/min whereas threshold frequencies varied from 9.2 to 40 pulses per train. No correlation was found between these two aspects of self-stimulation. The majority of threshold estimates lay within the range of 10 to 20 pulses per train, suggesting a relatively homogenous distribution of rewarding stimulation efficacy within the positive areas. The lowest threshold estimates are comparable to those usually obtained for the lateral hypothalamus, suggesting that the amygdala is an important focus for self-stimulation. In a second experiment, the effect of concurrent stimulation of the amygdala and lateral hypothalamus was assessed using a curve-shift method. In general, combining equi-rewarding stimuli had no effect on self-stimulation rate and threshold. However, when current to the lateral hypothalamus was adjusted such that the hypothalamic pulses were subthreshold for self-stimulation, under concurrent amygdalo-hypothalamic stimulation, a dramatic increase in self-stimulation rate was obtained. The magnitude of this rate augmentation was positively correlated with hypothalamic pulse intensity, however, independent of the order of stimulus presentation and intrapulse pair interval. The rate enhancing effect of combining low intensity hypothalamic stimulation with threshold amygdaloid self-stimulation was subsequently investigated in a series of experiments. In the first experiment, subjects were given a choice between a pulse frequency yielding maximal amygdaloid rate and a series of higher pulse frequencies. Subjects consistently preferred the higher frequency values attesting that the maximal rate in the amygdaloid rate-frequency function was not constrained by a saturating reinforcing effect. In a second experiment, subjects were given a choice between amygdaloid stimulation and concurrent amygdalo-hypothalamic stimulation, using low intensity hypothalamic pulses. Subjects showed no preference for either stimulation condition, although rates were higher for the latter condition. These findings suggest that the maximal rate for amygdaloid stimulation was constrained by factors interfering with barpressing and that the effect of these factors was attenuated by co-activation of the lateral hypothalamus. The nature of this constraint was then investigated. Administration of Phenobarbital (10, 15 & 20 mg/kg; i.p.) mimicked the rate-enhancing effect of concurrent amygdalo-hypothalamic stimulation for 2 of the 4 subjects tested. This finding suggests that the hypothalamic pulses contributed to attenuate seizure activity accompanying amygdaloid self-stimulation. In a final experiment, amygdaloid self-stimulation rates were also increased by co-activation of rewarding sites in the rostral medial forebrain bundle but not the dorsal raphe suggesting an anatomical specificity of this effect. It is concluded that within the circumscribed area of brain stimulation reward the amygdala is a separate reward system, the behavioral expression of which can be modulated by concurrent activation of rewarding foci in the lateral hypothalamus or medial forebrain bundle.
Keywords: Biology, Neuroscience.